Жестокий: сборник / Михаил Веллер - Веллер Михаил Иосифович (Пароль, 2003)
Экземпляры: ф.14 (2007) / Инвентарный номер: 51007 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: В 27 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-4